Participatory Evaluation of Herbicides in Wheat in Western Terai, Nepal - Yadav, Mathura; Pandey, Bisheswor Prasad; Khatri, Narayan; Chaurasiya, Vishnu Prasad (Agronomy Journal of Nepal, 2022)
The yield losses due to weeds vary depending on the weed species, their density and environmental factors. For controlling weeds in wheat, the farmers rely on herbicides due to cost and time effectiveness. Keeping these facts in view a field experiment was conducted to identify appropriate herbicides for controlling weeds in wheat. The experiment was carried out at three locations of Kapilvastu, Rupandehi and Nawalparasi during 2016/17 and 2017/18. Pendimethalin 30 EC, Sulfosulfuron 30 g a.i ha-1 and control treatments were evaluated in the field of six farmers in an area of 330 m2 for each treatment and were replicated six times. Wheat variety Tilottama was planted in the experiment. The fertilizer was applied at the rate of 100:50:50 N: P2O5: K2O kg ha-1. Weed populations were recorded at 30, 60 and 90 days after sowing in an area of 0.25 m-2 at three spots of each treatment and growth, yield attributes and yield data of wheat were collected and data were analyzed using Genstat statistical package. In 2016/17 Pendimethalin 1 kg a.i. ha-1 and Sulsosulfuron @ 25 g a.i. ha-1 and control (no herbicide spray) treatments were significantly difference for plant height, spike m-2 and grain yield but not significant for spike length and 1000 grains weight at Bimiha, Bhagdari and Nadawa sites. Both herbicides were found effective in controlling weed population. Whereas in 2017/18 Pendimethalin 30 EC. 1 kg a.i. ha-1 as pre-emergence and sulfosulfuron 30 g a.i. ha-1 as post emergence herbicides were found effective to suppress weed population. Plant height, spike length and 1000 grains weight variables were not significant but spikes m-2 and grains yield were significant Based on the pooled results it could be concluded that Pendimethalin 1 kg a.i. ha-1 and Sulsosulfuron @ 25 g a.i. ha-1 herbicides were found effective in controlling weed population and increased yield attributes and yield in wheat crop over weedy check.